Physical fitness and level of body components in the 11-15-year old population in west Slovakia - Halmová, Nora; Kanásová, Janka; Šiška, Ľuboslav (Akademia Wychowania Fizycznego w Poznaniu)
Introduction. The purpose of this paper is to extend the existing knowledge about physical fitness of the current school population aged 11-15 and identify the relationships between physical fitness and body components. Material and Methods. The research was held with the participation of 375 elementary pupils (5-9 grade).All measurements were done under identical conditions and were the part of the HBSC (Health and Behavior of School Age Children) study. The evaluation of physical fitness was done with the Ruffier test and SUUNTO POD testers were used to measure the heart rate. The data on body components were acquired with a bioimpedance diagnostic device InBody 720. Results. The results pointed to a lower physical fitness in girls (Ruffier index of 15.80 ± 4.2) than boys (14.78 ± 4). When comparing the individual grades, the level of physical fitness increased in boys and girls with the increasing age in the seventh grade and subsequently decreased, and the differences were statistically significant (p < 0.05). In the analyzed schools, the Ruffier index values were within the range of 13.9 ± 3.8 to 16.1 ± 4.5, and the differences between them were statistically significant (p < 0.05).The parameter values for body components followed the trend in the Ruffier test. The regression analysis showed that physical prowess is affected by body fat mass to 9.67% and total body water to 1.21%. Conclusions. Young generation at age 11 to15 years reaches lower physical fitness in comparison with the past. Boys have higher level of physical fitness than girls and the size of the city affects body composition and physical fitness. Parameters of body composition are in relation with Ruffier index. Body fat mass and total body water explaining the results of Ruffier test.
Keywords: bioimpedance; heart rate; physical fitness; Ruffier test